Validation of Aeroelastic Actuator Line for Wind Turbine Modelling in Complex Flows - Hodgson, Emily L.; Grinderslev, Christian; Meyer Forsting, Alexander R.; Troldborg, Niels; Sørensen, Niels N.; Sørensen, Jens N.; Andersen, Søren J. (Frontiers in Energy Research, 2022)
The actuator line method is a widely used technique to model wind turbines in computational fluid dynamics, as it significantly reduces the required computational expense in comparison to simulations using geometrically resolved blades. Actuator line coupled to an aeroelastic solver enables not only the study of detailed wake dynamics but also aeroelastic loads, flexible blade deformation and how this interacts with the flow. Validating aeroelastic actuator line predictions of blade loading, deflection and turbine wakes in complex inflow scenarios is particularly relevant for modern turbine designs and wind farm studies involving realistic inflows, wind shear or yaw misalignment. This work first implements a vortex-based smearing correction in an aeroelastic coupled actuator line, and performs a grid resolution and smearing parameter study which demonstrates significant improvement in the blade loading and in the numerical dependencies of predicted thrust and power output. A validation is then performed using a 2.3 MW turbine with R = 40 m radius, comparing against blade resolved fluid-structure interaction simulations and full-scale measurement data, in both laminar and turbulent inflows including both high shear and high yaw misalignment. For an axisymmetric laminar inflow case, the agreement between blade resolved and actuator line simulations is excellent, with prediction of integrated quantities within 0.2%. In more complex flow cases, good agreement is seen in overall trends but the actuator line predicts lower blade loading and flapwise deflection, leading to underpredictions of thrust by between 5.3% and 8.4%. The discrepancies seen can be attributed to differences in wake flow, induction, the reliance of the actuator line on the provided airfoil data and the force application into the computational domain. Comparing the wake between coupled actuator line and blade resolved simulations for turbulent flow cases also shows good agreement in wake deficit and redirection, even under high yaw conditions. Overall, this work validates the implementation of the vortex-based smearing correction and demonstrates the ability of the actuator line to closely match blade loading and deflection predictions of blade resolved simulations in complex flows, at a significantly lower computational cost.